2003
DOI: 10.1016/s0014-5793(03)00904-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced in vivo delivery of antisense oligonucleotides to restore dystrophin expression in adult mdx mouse muscle

Abstract: The use of antisense oligonucleotides (AOs) to induce exon skipping leading to generation of an in-frame dystrophin protein product could be of bene¢t in around 70% of Duchenne muscular dystrophy patients. We describe the use of hyaluronidase enhanced electrotransfer to deliver uncomplexed 2P P-Omethyl modi¢ed phosphorothioate AO to adult dystrophic mouse muscle, resulting in dystrophin expression in 20^30% of ¢bres in tibialis anterior muscle after a single injection. Although expression was transient, many o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 29 publications
1
32
0
Order By: Relevance
“…The microdystrophin line shows a level of dystrophin expression at the sarcolemma similar to that seen in the minidystrophin line when using rabbit polyclonal DysC3750 over a range of dilutions. 20,28 As shown in Figure 2b, at a dilution of 1:2000, the endogenous signal in the C57/Bl10 wild-type mouse tissue and in revertant fibres in the mdx is still clearly visible, but staining of the transgene product is not detectable in the transgenic line (Figure 2b). …”
Section: Analysis Of the Microdystrophin Transgenic MDX Linementioning
confidence: 96%
See 2 more Smart Citations
“…The microdystrophin line shows a level of dystrophin expression at the sarcolemma similar to that seen in the minidystrophin line when using rabbit polyclonal DysC3750 over a range of dilutions. 20,28 As shown in Figure 2b, at a dilution of 1:2000, the endogenous signal in the C57/Bl10 wild-type mouse tissue and in revertant fibres in the mdx is still clearly visible, but staining of the transgene product is not detectable in the transgenic line (Figure 2b). …”
Section: Analysis Of the Microdystrophin Transgenic MDX Linementioning
confidence: 96%
“…20 For the detection of revertant fibres or transfected dystrophin-positive fibres above the endogenous transgene expression levels, DysC3750 was titred down to a dilution of 1:2000, a level at which this antibody shows no dystrophin detection in the minidystrophin line. 28 Primary antibodies were diluted in PBST plus 1% FCS. Bound antibody was detected with an appropriate biotinylated species specific secondary antibody (Dako, Ely, UK) at 1:500 in PBST, followed by a 30 min incubation with horseradish peroxidaseconjugated streptavidin/biotin complex (ABC-HRP, Vector Laboratories, Peterborough, UK).…”
Section: Dystrophin Immunostainsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have demonstrated that electroporation can also be used to deliver oligonucleotides to muscle, specifically for antisense-mediated exon skipping in dystrophic skeletal muscle. 20 Electroporation has been extensively tested for gene transfer into tumours. Even the transfer of empty plasmid vector is sufficient to cause significant tumour regression in some models.…”
Section: Application Of An Electrical Field Dramatically Enhances Plamentioning
confidence: 99%
“…The significant advantage of AONs is the ability to target the gene irrespective of its large size and clinical applicability as small-molecule based therapy [9]. However, efficient delivery of AONs in muscles is a great challenge and much depends on the carriers that provide protection against degradation, cell specificity and release [10][11][12].…”
Section: Introductionmentioning
confidence: 99%